2020
DOI: 10.1177/2309499020930291
|View full text |Cite
|
Sign up to set email alerts
|

Controversies with nonoperative management for adolescent idiopathic scoliosis: Study from the APSS Scoliosis Focus Group

Abstract: Purpose: To determine consensus among Asia-Pacific surgeons regarding nonoperative management for adolescent idiopathic scoliosis (AIS). Methods: An online REDCap questionnaire was circulated to surgeons in the Asia-Pacific region during the period of July 2019 to September 2019 to inquire about various components of nonoperative treatment for AIS. Aspects under study included access to screening, when MRIs were obtained, quality-of-life assessments used, role of scoliosis-specific exercises, bracing criteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The Risser staging system is often criticized for its inaccuracy [38], but it is still commonly used for guiding brace prescription and weaning. Many clinicians may use other skeletal maturity indices in addition to the Risser staging system to improve and facilitate more precise growth assessments, such as using the physeal closure at the knee, the phalanges, and the distal radius and ulna visible on the handwrist radiograph [8,12,16,32]. This can only be achieved by understanding how skeletal maturity indices behave and their effectiveness in evaluating growth.…”
Section: Discussionmentioning
confidence: 99%
“…The Risser staging system is often criticized for its inaccuracy [38], but it is still commonly used for guiding brace prescription and weaning. Many clinicians may use other skeletal maturity indices in addition to the Risser staging system to improve and facilitate more precise growth assessments, such as using the physeal closure at the knee, the phalanges, and the distal radius and ulna visible on the handwrist radiograph [8,12,16,32]. This can only be achieved by understanding how skeletal maturity indices behave and their effectiveness in evaluating growth.…”
Section: Discussionmentioning
confidence: 99%
“…Brace weaning can be a slow process whereby daily brace-wear hours are gradually reduced or changed to night use only vs a rapid immediate brace removal. Some clinicians err on the side of gradual weaning to be certain that curves remain stable after some months of reduced brace hours, whereas others prefer immediate weaning for earlier return to normality with complete resumption of exercises, muscle training, and activity level . The main rationale for gradual weaning over a 6-month period is to allow spine adaptation to the unloaded environment while still maintaining the corrective posture.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinicians err on the side of gradual weaning to be certain that curves remain stable after some months of reduced brace hours, whereas others prefer immediate weaning for earlier return to normality with complete resumption of exercises, muscle training, and activity level. The main rationale for gradual weaning over a 6-month period is to allow spine adaptation to the unloaded environment while still maintaining the corrective posture. The benefit of gradual weaning is unclear, but immediate weaning may lead to worse Cobb angle and truncal imbalance and may be associated with worse HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that nonsurgical therapy is an effective treatment for scoliosis, particularly AIS ( Dufvenberg et al, 2021 ; Ng et al, 2017 ). However, the prevalence of scoliosis is increasing, and many researchers argue that current treatments for AIS are insufficient ( Cheung et al, 2020 ; Płaszewski and Bettany-Saltikov, 2014 ).…”
Section: Introductionmentioning
confidence: 99%